A histone H3K4me1-specific binding protein is required for siRNA accumulation and DNA methylation at a subset of loci targeted by RNA-directed DNA methylation - Qingfeng Niu (Nature Portfolio, 2021)
In plants, RNA-directed DNA methylation (RdDM) is a de novo DNA methylation pathway that is responsible for transcriptional silencing of repetitive elements. Here, the authors characterized a new RdDM factor, RDM15, and show that it is required for RdDM-dependent DNA methylation and siRNA accumulation at a subset of RdDM target loci.